Training on the Use of the Interpulse Application for Digitizing Elderly Health Data Collection at Posbindu: Community Service - Wenny Desty Febrian; Bias Yulisa Geni; Era Agita Kabdiyono (Siber Nusantara Research, 2026)
The digitalization of elderly health data collection has become increasingly important in supporting more effective, systematic, and sustainable health information management at the community level. Conventional record-keeping practices continue to face several challenges, particularly in data storage, retrieval, updating, and processing. This Community Service (PkM) program aimed to enhance community knowledge and digital literacy through training on the use of the Interpulse application as a supporting tool for the digitalization of elderly health data collection at Posbindu. The activity was conducted face-to-face on June 12, 2026, in Duri Selatan District, Jakarta, and involved 25 participants from the surrounding community. The implementation consisted of several stages, including preparation, material delivery through presentations, question-and-answer sessions and discussions, evaluation, and follow-up activities. The training materials covered the importance of digital health data management, limitations of manual recording systems, the benefits of digital data management, and an introduction to the functions of the Interpulse application. The results indicated positive responses and active participation from the participants throughout the training. Participants demonstrated improved understanding of the importance of managing health information digitally and recognized the potential of the Interpulse application to facilitate elderly health data collection. The activity also identified the need for continuous assistance due to differences in participants’ levels of digital literacy and previous experience with technology. Overall, the training contributed to strengthening community awareness and readiness to adopt digital technology for elderly health data management. Further implementation through hands-on practice, mentoring, and monitoring is recommended to ensure the sustainability and effective utilization of the Interpulse application in Posbindu activities.